2016
DOI: 10.1002/hep.28571
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Disease Burden in the United States in the era of oral direct‐acting antivirals

Abstract: Oral direct-acting antivirals (DAAs) represent a major advance in hepatitis C virus (HCV) treatment. Along with recent updates in HCV screening policy and expansions in insurance coverage, the treatment demand in the United States is changing rapidly. Our objective was to project the characteristics and number of people needing antiviral treatment, and HCV- associated disease burden in the era of oral DAAs. We used a previously developed and validated Hepatitis C Disease Burden Simulation model (HEP-SIM). HEP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 26 publications
1
126
0
4
Order By: Relevance
“…In the nearest years, however, it will be largely driven by treatment capacity, which is changing rapidly. 66 Similar studies from Europe and Asia have confirmed the tremendous economic burden of chronic HCV infection. A report from Italy suggested the total nationwide Economic Burden of Hepatitis C Infection burden of approximately V1 billion annually (as of 2013), with less than 40% of it being allocated for direct medical expenses.…”
Section: The Cost Of Hepatitis C Virus-related Liver Diseasementioning
confidence: 67%
See 2 more Smart Citations
“…In the nearest years, however, it will be largely driven by treatment capacity, which is changing rapidly. 66 Similar studies from Europe and Asia have confirmed the tremendous economic burden of chronic HCV infection. A report from Italy suggested the total nationwide Economic Burden of Hepatitis C Infection burden of approximately V1 billion annually (as of 2013), with less than 40% of it being allocated for direct medical expenses.…”
Section: The Cost Of Hepatitis C Virus-related Liver Diseasementioning
confidence: 67%
“…65,66 In 1 study from the United States, the authors projected a decrease in the infection prevalence of nearly 50% by 2020 in comparison with 2015, and of 70% by 2030; notably, the projected remaining prevalence would be primarily owing to people being unaware of their infection and, thus, the cost-effectiveness of universal screening will probably have to be revisited. 67,68 The decrease in adverse outcomes is expected to follow at a slower pace, with a 20% to 35% reduction by 2020 in the numbers of liver-related deaths, new cases of decompensated cirrhosis, hepatocellular carcinoma and HCV-associated liver transplantations 66 ; the disparity in the changes of the prevalence of the infection and of its adverse sequelae might be explained by a disproportionally higher prevalence of HCV positivity in older patients at present. 69 Given that, the direct economic burden of HCV infection is also expected to decrease proportionally.…”
Section: The Cost Of Hepatitis C Virus-related Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Pode ser detectado no plasma em alguns dias de exposição, muitas vezes 1 a 4 semanas, sendo que os picos de viremia costumam ocorrer nas primeiras 8 a 12 semanas de infecção e depois sua quantidade cai para níveis indetectáveis, porém, na maioria dos casos a infecção persiste e se torna crônica. Essa infecção persistente parece ser devida a fracas respostas das células T CD4 + e CD8 +, que não conseguem controlar a replicação viral 24,29 . Estudos recentes demonstram que na forma crônica, o HCV, por si só, tem pouca ação citopática, sendo que a resposta inflamatória local vai desencadear a fibrose e as alterações hepáticas comumente visualizadas nesse quadro.…”
Section: Epidemiologiaunclassified
“…A maioria dos pacientes (80-85%) que se infectam de forma aguda não se curam e progridem para infecção crônica 23 . Os objetivos do tratamento visam à erradicação viral, atrasar a progressão da fibrose, aliviar os sintomas, prevenir complicações, minimizar a mortalidade por causa e, em última análise, maximizar a qualidade de vida 24 . Este artigo tem como finalidade somar informações relevantes sobre as hepatites virais causadas pelo HBV e HCV, principalmente no que tange diagnóstico e tratamento dessa patologia de extrema importância em nosso meio.…”
Section: Introductionunclassified